(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
A transformation of higher education in Indonesia with a change in curriculum to MBKM presents new challenges in producing quality graduates. The Indonesian government recommends the PjBL model, and it has been studied with various integrations to improve the quality of learning in Indonesia. The quality of learning is influenced by the learning and teaching styles of students through specific learning techniques. This study aims to analyze the impact of STEAM Education on 21st-century skills (6C). First, the synergy between PjBL, Ethnoscience, STEAM, Multiple Intelligences, and Multiple Representations will be determined by analyzing articles from 2014 to 2024 using the systematic literature review method. The Systematic Literature Review method is a research stage to process 966 articles with 4,562 relevant words in Publish or Perrish 8 Software, and the data results are selected in Bibliometric VosViewers Software. The findings are PjBL integration research (2014-2024) in the form of the synergy of PjBL-Ethno-STEAM-MIR aspects in quantum synergy modelling—conclusion, classified against 6C skills as the impact of STEAM education in 21st-century skills. Further research is expected to develop the PjBL-Ethno-STEAM-MIR model and its teaching materials.